ANALISA PENGUJIAN SISTEM INFORMASI RUMAH SAKIT (STUDI KASUS RUMAH SAKIT KHUSUS BEDAH AN-NUR YOGYAKARTA) - Ulinnuha Yudiansa Putra (Optimum: Jurnal Ekonomi dan Pembangunan, 2013)
Information technology system can be used to facilitate data processing companies, speeding up transaction processing to be used as a managerial decision-making. An information technology system can be said to be successful or suitable for use by the firms if they meet certain factors. DeLone and McLean (2003) has provided an overview of the factors that can be used to assess whether an appropriate information system has been used in a company. Factors used in this study is the Quality Systems, Information Quality, Service Quality, User Satisfaction and Net Benefits. This research was conducted at the Hospital for Special Surgery AN NUR Yogyakarta. The object that is used is SIMRS (Hospital Management Information System) used by respondents are 50 employees who use SIMRS Hospital in support of the work. The analytical tool used in this study is to Partial Least Square (PLS). The results showed that the quality of information, quality of service and user satisfaction significantly influence the net benefits while not affecting the quality system net benefits.